ENTRE O GROTESCO E O SUBLIME: O TRÁGICO E O CÔMICO NO EVANGELHO DE MARCOS - SANTOS, PAULO SÉRGIO MACEDO DOS (2018)
The present dissertation seeks to highlight the diversity of genres that make up the Gospel of Mark, through concepts provided by literary criticism, the way these elements were used in the different layers of the text, and thus, to denote the tragic and comic traits in the text, their elements of grotesque and sublime. The gaps left by the research on the Gospel of Mark, which at first was small and somewhat neglected, gained ground in the last decades. The text, which was considered by researchers as a summary of Matthew's gospel, gained some prominence with the premise of its precedence over the synoptic gospels and their dependence on Mark's text. If sometimes these facts made the research dif-ficult, by others it opened space to seek in other areas of knowledge the theoreti-cal and bibliographic references. We seek to highlight some of the tragic traits in Mark's narrative. The construction of the protagonist as a tragic character, who is aware of his tragicity, his martyrdom and death are addressed in this chapter. We study two cases that are configured as voices of the choir, their location and the function of validating the Messiah through the public voice. Miracles are treated as accelerating elements of the narrative, a kind of deux-ex-machina, to which Aristotle perceived in his Poetics. It was also tried to evidence the existence of laughter in the Gospel of Mark. Through concepts of laughter theorists such as Minois and Bergson, we start from these, in an attempt to locate some case, in which the presence of irony, grotesque and sarcasm as forms of laughable in Mark's account. The demoniac Geraseno and the dialogue with the Phoenician Syrian woman are treated in this chapter, and their humorous traits are evident. We finally came to the conclusion that Mark's Gospel is a hybrid text, of popular culture and therefore, multicultural and with a diversity of styles. The Bakhtin carnivalesque theory, Lotman's semiosphere, and Victor Hugo's romanticism in his conception of the union of the grotesque and the sublime are all to this un-derstanding